Saving, Pension Contributions, and the Real Interest Rate - Makin, John H.; Couch, Kenneth A. (The Review of Economics and Statistics, 1989)
A test of the hypothesis that estimates of the interest elasticity of personal and private saving may be biased downward by a failure to control for behavior related to defined benefit pension programs fails to reject existence of a positive interest elasticity of private saving. Correcting for pension funding bias, the estimated interest elasticity of private saving is 0.04, well below Michael J. Boskin's (1978) estimate of 0.4 obtained with a different data set and different estimation procedures. The estimated interest elasticity of personal saving is 0.28. Copyright 1989 by MIT Press.